Relationship between plate mass and actual leg press loads - Clemons, J. (The Journal of Strength and Conditioning Research, 2010)
When using a typical leg press machine there is no way of knowing the actual weight that is lifted. The only information available to the lifter is the added plate mass and perhaps sled weight if the manufacturer's specifications are available. Unfortunately, knowledge of sled weight is not very helpful because a portion of that weight is supported by the frame. The purpose of this study is to determine accurate resistance loads beginning first with only the sled and then progressively adding 4.54 kg up to a maximum load of 454.55 kg. A load cell was attached to the frame of an LE408 BM Leg Press Machine and oriented so that it was in the same slide plane as the sled. It was calibrated by the manufacturer to the control unit that accompanied it and, according to specifications, is accurate to +/- 0.2 kg and has a maximum capacity of 453.5 kg. The sled was pushed from its supports and hooked to the lower portion of a chain serially attached to the load cell and upper frame. The data acquisition system was zeroed out to eliminate the weight of the load cell and the lower chain. The sled was slowly lowered until the weight of the sled and any added weight was fully supported by the load cell. Once motionless, the measurement system was subsequently activated at a sampling rate of 40 measurements [middle dot] sec-1. Peak measurements were captured by the control unit. Pearson Product Moment correlation was used to determine the relationship between plate mass and the associated peak force measures captured from the system beginning with 4.54 kg up to 454.55 kg: (r = 1), p = 0.000. Results indicated that when 0 plates were on the machine, the lifter must overcome 49.6 kg of resistance to move the sled. As plate mass increased, resistance also increased. The ratio of plate mass to load lifted began at 0.086 with two 2.27 kg plates on the apparatus and gradually increased to 1.00 with 140.9 kg of plate mass and a measured resistance of 140.7 kg. Up to this point, the measured resistance exceeded total plate mass due to the additive sled component; however, beyond 140.9 kg of plate mass ratios began to exceed 1 presumably due to progressively more weight being transferred to the frame. At 454.55 kg (1000 lbs) on the machine, the actual resistance that would be overcome by a lifter would be 342.1 kg (752.6 lbs) at a ratio of 1.329. The linear regression formula generated was: Mass lifted = (0.64 [middle dot] total plate mass in kg) + 50.26 kg. Obtaining accurate knowledge of lifting loads will have testing benefits and will likely produce better estimates of free weight squatting ability.